Expression of IL-10 and Caspase-3 in Alveolar Bone after Topical Administration of Sodium Fluoride (Naf) Gel in Orthodontic Tooth Movement - Rina Sutjiati; Sulistyani Sulistyani; Erna Sulistyani; Rudy Joelijanto; Annisa Syifa M.; Hasna' Fakhriyah J. (Health Notions, 2022)
The success of orthodontic treatment can be achieved through tissue, cellular and molecular mechanisms due to mechanical stimuli formed by the pressure side and the tension side. Sodium Fluoride (NaF) is known to increase the bone formation process in the area of attraction in vitro and in vivo. The study aimed to determine sodium fluoride (NaF) against Caspase-3 by osteoblasts and IL-10 by osteoclasts in alveolar bone remodeling on orthodontic tooth movement. The research applied laboratory experiment using 16 male Wistar rats. Rats were divided into two groups; group C: given orthodontic strength without NaF; and group T: given orthodontic strength with NaF. Variable measurements were carried out after the 7th and 14th day. The data was statistically tested using One-Way Anova test analysis (p ≤0.05) to compare the mean number of expressions of both groups C and T. The number of osteoclasts expressing IL-10 was significantly higher in group T when compared to that of group C while the number of osteoblasts expressing Caspase-3 was smaller in group T when compared to that of group C. NaF can increase IL-10 expression in osteoclasts and decrease Caspase-3 expression by osteoblasts on orthodontic tooth movement. Keywords: Caspase-3; IL-10; sodium fluoride (NaF); immunohistichemistry